Plaque erosion is a major substrate for coronary thrombosis in acute myocardial infarction. (1st September 1999) - Arbustini, E; Dal Bello, B; Morbini, P; Burke, A P; Bocciarelli, M; Specchia, G; Virmani, R
Abstract : OBJECTIVE: To evaluate the prevalence of plaque erosion as a substrate for coronary thrombosis. DESIGN: Pathological study in patients with acute myocardial infarction not treated with thrombolysis or coronary interventional procedures. PATIENTS: 298 consecutive patients (189 men, mean (SD) age 66 (11) years; 109 women, 74 (8) years) dying in hospital between 1984 and 1996 from acute myocardial infarction, diagnosed by ECG changes and rise in cardiac enzymes. MAIN OUTCOME MEASURES: Histopathological determination of plaque erosion as substrate for acute thrombosis; location and histological type of coronary thrombosis; acute and healed myocardial infarcts; ventricular rupture. RESULTS: Acute coronary thrombi were found in 291 hearts (98%); in 74 cases (25%; 40/107 women (37.4%) and 34/184 men (18.5%); p = 0.0004), the plaque substrate for thrombosis was erosion. Healed infarcts were found in 37.5% of men v 22% of women (p = 0.01). Heart rupture was more common in women than in men (22% v 10.5%, p = 0.01). The distribution of infarcts, thrombus location, heart rupture, and healed infarcts was similar in cases of plaque rupture and plaque erosion. CONCLUSIONS: Plaque erosion is an important substrate for coronary thrombosis in patients dying of acute myocardial infarction. Its prevalence is significantly higher in women than in men.